Peningkatan Kesejahteraan Desa Blederan melalui Pemberdayaan dan Pengembangan Kualitas Sumber Daya Manusia - Julitawaty, Wily; Kurniawan, Naufal; Junaedi, Muhammad (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The Community Service Program in Blederan Village, Mojotengah District, Wonosobo Regency, Central Java, aims to look closely at the socio-cultural conditions of the community on the highest plateau of the island of Java. This activity emphasizes understanding and motivation for the residents of Blederan Village, encouraging them to continue their education in order to improve welfare and accelerate development in the village. A multidimensional approach is applied in the fields of education, economics, health, environment and culture. The service method involves education, training and coaching activities directly to the community. The main focus is to provide insight into the importance of education, economic empowerment, attention to health, environmental preservation, and development of local culture. The results of the service include increasing public understanding of the importance of education, economic growth through small and medium businesses, improving health conditions, sustainable environmental management practices, as well as preserving and developing local culture. This program is expected to have a positive impact in improving the quality of life and welfare of the people of Blederan Village.